The Day After. Considerations and Future Prospects for Studying the Phenomenon of Othering after Jihadist Terrorist Attacks - Conti, Uliano (Italian Sociological Review, 2018)
The paper defines the Othering phenomenon in a sociological perspective. This phenomenon can be contextualised starting from the concept of Orientalism and addressed with reference to sociological theories and concepts. Aim of the article is to propose the concept of Othering and the analysis of the processes of Othering as a key to responding to the consequences of the jihadist terrorist strategy in the West. After September 11, 2001 and after the terrorist attacks in Europe, in fact, citizens of Middle Eastern and Arab origin have been victims of processes of Othering and social exclusion because of their ethnic origin. This paper considers some empirical research on the processes of Othering. The main referenced sociological theories and concepts are highlighted for each empirical research taken into consideration, with attention given to the role of visual perception in favoring the processes of Othering. Media, television and films as well as online platforms, thanks to visual tools and contents, use stereotypes when portraying people of Middle Eastern and Arab origin. The article examines how the processes of Othering originate from the sensory path of sight. Finally, it emerges that to date the theme of Othering has not yet been placed in a general field of theory in sociological literature. Each considered empirical research focuses on a particular concept or theory, thus reducing the complexity of the Othering phenomenon. The study of the processes of Othering to be set in a complex theory of otherness, takes shape as a sociological key to respond to important social challenges, such as terrorism.